TWO LANGUAGES, TWO CULTURES, ONE MIND: A STUDY INTO DEVELOPMENTAL CHANGES IN THE STUDENTS’ VIEW OF LANGUAGE AS A TOOL IN CROSS-CULTURAL COMMUNICATION - Whyatt, Bogusława (Versita Ltd., de Gruyter, 2007)
In this paper I report on the preliminary results of a longitudinal one-year study of students’ progression from a low level of language awareness manifested in their superficial/intuitive use of language/languages to a higher level of language self-awareness manifested in their more con- trolled use of language. The data gathered for this study include four sources: a language aware- ness questionnaire, think aloud protocols, error analysis and post error analysis in-class discussions. The results of this study are intended to be further explored in a larger research project.
Keywords: linguistic self-awareness; language control; translation; bilingual language processing; translation training